Digestive proteases of Morelet’s crocodile (Crocodylus moreletii) in three life stages - Castillo-Rodríguez, Manuel Alejandro (2024)
Introduction: Morelet’s crocodile (Crocodylus moreletii) is a species distributed in the Mexican southeast and threatened due to multiple pressures. Objective: To characterize the digestive proteases in the acid phase (stomach) and alkaline phase (intestine) of three life stages of C. moreletii in captivity (hatchling, juvenile, and adult). Methods: Total alkaline and acid protease activities were quantified using casein and haemoglobin as substrates. Trypsin, chymotrypsin, leucine aminopeptidase, and elastase activities were quantified using synthetic substrates. Protease profiles were analysed by SDS-PAGE and Native-PAGE. Results: The specific activity of acid and alkaline proteases showed differences between the three stages, finding the highest activity in the juveniles. Trypsin, chymotrypsin, leucine aminopeptidase, and elastase activities were higher in hatchlings. There were differences in optimum pH and temperature of acid and alkaline proteases, trypsin, and leucine aminopeptidase between the three stages, demonstrating the diversification of the enzymes according to different stages, as well as the presence of specific isoforms in each stage of C. moreletii. The acid phase zymogram showed four bands with pepsin-like acid activity in the hatchling and juvenile crocodile, while in the adult only two of the four bands were detected. The alkaline zymogram showed that the hatchling had the highest number of activity bands compared to the other stages, corresponding to the high specific activity reported in the alkaline phase. Conclusions: Digestive proteases of Morelet’s crocodile differ in their biochemical characteristics and the number of proteases between hatchling, juvenile, and adult. This could help in the future design of balanced diets as well to the sustainable management and production of this species.